(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
The tensions that agitate the political sphere of a certain space and that contaminate, or fracture, both social life and the processes of the symbolic representation can manifest themselves, with greater or less emphasis, both in the choice of certain generic and scriptural paths and in the transformations and/or modifications that literary texts can undergo.